Aging, obesity, sarcopenia and the effect of diet and exercise intervention - Colleluori, Georgia; Villareal, Dennis T. (Experimental gerontology, 2021)
The number of adults 65 years and older is increasing worldwide and will represent the 20% of the population by 2030. Half of them will suffer from obesity. The decline in muscle mass and strength, known as sarcopenia, is very common among older adults with obesity (sarcopenic obesity). Sarcopenic obesity is strongly associated with frailty, cardiometabolic dysfunction, physical disability, and mortality. Increasing efforts have been hence made to identify effective strategies able to promote healthy aging and curb the obesity pandemic. Among these, lifestyle interventions consisting of diet and exercise protocols have been extensively explored. Importantly, diet-induced weight loss is associated with fat, muscle, and bone mass losses, and may further exacerbate age-related sarcopenia and frailty outcomes in older adults. Successful approaches to induce fat mass loss while preserving lean and bone mass are critical to reduce the aging- and obesity-related physical and metabolic complications and at the same time ameliorate frailty. In this review article, we discuss the most recent evidence on the age-related alterations in adipose tissue and muscle health and on the effect of calorie restriction and exercise approaches for older adults with obesity and sarcopenia, emphasizing the existing gaps in the literature that need further investigation. •Obesity and sarcopenia are common in older adults and are associated with frailty, disability and mortality.•Aging causes specific adipose tissue and skeletal muscle dysfunctions that can be prevented by lifestyle interventions.•Diet-induced weight loss causes fat and muscle mass reduction, exacerbating the age-related sarcopenia.•Diet plus specific exercise types can prevent muscle loss and improve the age-related adipose tissue and muscle dysfunctions.